Percepção de alunos do 5º ano do ensino fundamental sobre meio ambiente - SAMPAIO, Kelly Cristina Rocha (2020)
The present work had the objective of analyzing the perception about the Environment of students of the 5th year of elementary school in a school in partnership with the Federal Rural University of Amazonia (UFRA), located in the neighborhood of Terra Firme, in the city of Belém. The 24 students in this class were divided into six groups with four members in each group. Each group answered freely the three questions on the Environment, two of them oriented to be answered by means of drawings. The results obtained revealed that although the "Nature" category has a strong expressiveness through the drawings, the category "Environmental Problems" also had great representativity in the written answers, in which the students demonstrated to be aware of the “Environmental Problems” with respect to the waste disposal.